2012
DOI: 10.1016/j.aju.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The value of percentage free prostate specific antigen (PSA) in the detection of prostate cancer among patients with intermediate levels of total PSA (4.0–10.0 ng/mL) in Nigeria

Abstract: Objectives To assess the value of percentage free prostate-specific antigen (%fPSA) in the detection of prostate cancer among Nigerian men with an intermediate total PSA level (4–10 ng/mL), and to show if the optimum threshold for biopsy is different from Caucasian values when the widely used (six-core, digitally directed) prostate biopsy protocol in Nigerians is applied. Patients and methods The study included 105 patients aged >50 years, with a palpably benign prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…However, these parameters are not 100% accurate in discriminating between low- and high-risk patients, indicating the need for companion biomarkers to better predict disease evolution and improve patient stratification. Although PSMA is a promising biomarker in that it is more specific than PSA, its role in PCa diagnosis and evolution has yet to be confirmed 2 , 3 . In fact, differences in PSMA expression in terms of cellular or tissue localization may depend on the type of antibody used or sample analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these parameters are not 100% accurate in discriminating between low- and high-risk patients, indicating the need for companion biomarkers to better predict disease evolution and improve patient stratification. Although PSMA is a promising biomarker in that it is more specific than PSA, its role in PCa diagnosis and evolution has yet to be confirmed 2 , 3 . In fact, differences in PSMA expression in terms of cellular or tissue localization may depend on the type of antibody used or sample analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, serum PSA is burdened by low accuracy because it is an organ-specific rather than tumor-specific biomarker and can also show an abnormal increase in the presence of benign prostatic hyperplasia. This is one of the most important limitations of PSA for diagnostic/prognostic purposes 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows that in the intermediate zone the occurrence of prostate cancer is higher in those individuals with low prostate volume. [14][15][16] PSA was approved by Food and Drug Administration (FDA) for use in prostate screening way back in 1994 and it is the most commonly used parameter for prostate cancer screening in the United States. 1,17,18 Catalona et al in a metacentric study done on 6,374 men of 50 years of age and older showed that 72% or (93/130) of prostate cancers detected by PSA and DRE were organ-confined indicating an early stage of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results for prostate volume obtained using transabdominal ultrasonography are as stated in the Results and discussion sections [3] . Unlike with standard TRUS, an accurate measurement of prostate volume for further analysis of volume was not possible because transabdominal scans of the prostate were used.…”
Section: Replymentioning
confidence: 99%